ITSSOIN hypotheses: deliverable D1.4 of the project: “Impact of the Third Sector as Social Innovation” (ITSSOIN), European Commission - 7th Framework Programme - Anheier, Helmut K.; Krlev, Gorgi; Preuß, Stina; Mildenberger, Georg; Bekkers, René; Lund, Anker Brink (European Commission, 2014)
This report brings together findings from the first ITSSOIN project working steps to formulate empirically testable hypotheses on the impact of the third sector and social innovation - in particular regarding the role of the third sector in generating social innovation but also with reference to framework conditions. Our analysis includes the following different levels: (1) organisational properties, (2) volunteering and volunteers, (3) institutional frameworks, (4) citizen perceptions and media influence. For each level we take into account empirical findings and theoretical insights in order to develop a more detailed understanding of how the third sector’s social innovation potential can be captured. Furthermore, we outline how the hypotheses will be tested in separate work steps of the ITSSOIN project.